Enhancing Marketing Strategies for the Serati Banten Ritual Group in Desa Adat Sading, Mengwi, Badung Regency - Ketut Sudarmini; Gusti Ayu Sugiati; I Dewa Ayu Eka Pertiwi (PT FORMOSA CENDEKIA GLOBAL, 2023)
A Serati Banten Group led by Jero Mangku Suparmi in Desa Adat Sading efficiently fulfills ritual requests. Collaborative efforts among various groups yielded successful 2022 results. To boost income, they must expand market reach via social media like Instagram, Facebook, and WhatsApp. Standardizing banten pricing across Serati Banten Groups is crucial. Each group determines cost prices for various banten types to set consumer prices. Consequently, we support Mangku Suparmi's group in Desa Adat Sading by enhancing digital marketing strategies for ritual and banten promotion.